The Effect of Ascorbic Acid on the Quality of Fresh Cut Pineapple (Ananas comosus (L.) Merr ) Stored at 5°C - Ayu Lestari; Siti Aisyah A; Khair Hadriman (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Fresh-cut pineapple is increasingly popular due to its convenience and high nutritional value. This study evaluatedthe effects of different concentrations of ascorbic acid on the quality of fresh-cut pineapple (Ananas comosus L.var. MS16) stored at 5 °C by analyzing hardness, color parameters (L*, a*, b*, chroma, hue angle), soluble solidscontent, sugar/acid ratio, ascorbic acid content, and total titratable acidity. Results showed that ascorbic acidhad no significant effect (p > 0.05) on hardness and color, indicating stable texture and appearance, butsignificantly affected (p < 0.05) the sugar/acid ratio, ascorbic acid content, and total titratable acidity. The 0.5%treatment best maintained texture (3.02 N), acidity (4.56% citric acid), and color stability, while the 1% treatmentproduced the highest vitamin C content (28.53 mg/100 g). The control exhibited the highest sugar/acid ratio(40.89), indicating a sweeter taste but lower antioxidant protection. Overall, 0.5% ascorbic acid was the mosteffective concentration for preserving freshness and nutritional quality during cold storage.